"Savage" hair and mothers' hearts: a corpus-based critical discourse analysis of intersectional identities in two South African school setworks - Hubbard, Beatrice Elizabeth Anne (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2020)
This thesis reports on the discursive construal of intersectional physical identities, with particular reference to 'black' female characters, in two novels: Sindiwe Magona's Mother to Mother, and Edyth Bulbring's The Mark. These novels are prescribed for Grade 10 English Home Language learners in all South African public schools. Gendered identity construction in texts has been widely discussed in critical linguistics, with some research showing that the ways in which bodies are construed reveal the hegemonic and stereotypical gendering of men and women. However, these arguments have not adequately addressed the intersectional nature of identity construction. This thesis employs Corpus-based Critical Discourse Analysis to investigate the complex physical identities of, especially, 'black' female characters in these two novels. The inclusion of Corpus Linguistics is essential for uncovering hidden patterns of language choice, while the analytical techniques and theoretical notions from Critical Discourse Analysis provide the explanatory power that underpins the qualitative analysis. The uses to which nine key body parts are put reveal discourse prosodies showing different intersectional realisations for intimacy, power, violence, emotion, and racial marking. These discourse prosodies are most starkly realised in the two body parts, one from each novel, that are statistically most clearly linked to 'black' female characters. HAIR in The Mark is used variously as a racial marker, a target for racism, and a symbol for racial pride. HEART in Mother to Mother is used almost exclusively to symbolise the emotional pain of a mother's love, and how empathy for another mother's pain can bridge racial divides. Principal findings reveal that both novels provide very necessary lessons in cross-racial empathy, pride in 'blackness,' and interracial relationships. However, it is of concern that these novels also exhibit an over-valorisation of motherhood, largely stereotypical depictions of gender roles, and ableist language. In sum, both novels promote some of the transformative principles of the national curriculum, and are shown to have a bearing on nation building.
Keywords: Women in literature; Women, Black in literature; Critical discourse analysis; Magona, Sindiwe -- Mother to mother; Bulbring, Edyth -- The Mark